Causal role of plasma liposome in diabetic retinopathy: mendelian randomization (MR) study - Kai Yin; Lu Ding; Xueyan Li; Yuqi Zhang; Siyu Song; Liyuan Cao; Ruixue Deng; Min Li; Zirui Li; Qinjing Xia; Daqing Zhao; Xiangyan Li; et al. (Diabetology & Metabolic Syndrome)
Abstract Background Research indicates that there may be an association between plasma lipidome levels and the incidence of diabetic retinopathy (DR) in patients. However, the potential causality of this relationship is yet to be determined. To investigate this matter further, we employed a two-sample Mendelian randomization (MR) analysis to comprehensively assess the causality between lipidome levels and DR. Methods Summary statistics for lipid levels and DR were obtained from the Genome-Wide Association Studies (GWAS) Catalog database and the FinnGen Consortium, respectively. We conducted a two-sample MR analysis, and statistical analysis were performed using the inverse variance weighted (IVW) with the addition of the MR-Egger, weighted median (WM), constrained maximum likelihood and model averaging (cML-MA) to test for causal associations between lipid levels and DR. Heterogeneity was checked using Cochran’s Q statistic. The MR Pleiotropy Residual Sum and Outlier (MR-PRESSO) global test and the MR-Egger regression were used to detect horizontal pleiotropy. The robustness of our findings was assessed using leave-one-out and funnel plots. To further assess the reliability of the results, linkage disequilibrium score regressions, colocalization analysis and reverse MR analysis were also performed. Results Analysis of the pooled MR results and after correction for the false discovery rate (FDR) revealed that five lipid levels were associated with DR risk. Phosphatidylcholine (16:0_16:0) levels [OR = 0.869 (0.810 to 0.933), P fdr = 0.006], phosphatidylcholine (16:0_20:2) levels [OR = 0.893 (0.834 to 0.956), P fdr = 0.043] and phosphatidylethanolamine (18:0_20:4) levels [OR = 0.906 (0.863 to 0.951), P fdr = 0.006] were protective against DR, whereas sphingomyelin (d36:1) levels [OR = 1.120 (1.061 to 1.183), P fdr = 0.006], and sphingomyelin (d40:1) levels [OR = 1.081 (1.031 to 1.134), P fdr = 0.043] were associated with a greater risk of DR. Further sensitivity analysis did not reveal heterogeneity or horizontal pleiotropy. Conclusion In summary, genetic evidence suggests a causal relationship between the levels of specific lipid levels and DR. These findings may provide valuable insights into the causal relationships between lipid levels and DR, potentially informing future prevention and treatment strategies.